2017
DOI: 10.3390/f8090316
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Scots Pine Phyllosphere and Soil Fungal Communities during Outbreaks of Defoliating Insects

Abstract: Abstract:Outbreaks of forest pests increase with climate change, and thereby may affect microbial communities and ecosystem functioning. We investigated the structure of phyllosphere and soil microbial communities during defoliation by the nun moth (Lymantria monacha L.) (80% defoliation) and the pine tree lappet (Dendrolimus pini L.) (50% defoliation) in Scots pine forests (Pinus sylvestris L.) in Germany. Ribosomal RNA genes of fungi and bacteria were amplified by polymerase chain reaction (PCR), separated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Reference [26]). Briefly, the DNA from 50 mg of finely ground soil, needle, feces, and litter was extracted following a CTAB protocol with two chloroform/isoamylalcohol steps with an intermediate phenol purification [27] and subsequent polyethylene glycol precipitation [28].…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [26]). Briefly, the DNA from 50 mg of finely ground soil, needle, feces, and litter was extracted following a CTAB protocol with two chloroform/isoamylalcohol steps with an intermediate phenol purification [27] and subsequent polyethylene glycol precipitation [28].…”
Section: Dna Extractionmentioning
confidence: 99%
“…All the investigated forests were located in the federal state of Brandenburg, Germany. The detailed site and soil properties were described earlier [25,26]. The soil types at the study sites in both years were classified as podzols (Food and Agriculture Organization of the United Nations (FAO) classification) derived from glacial and aeolian medium sand deposits.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Both sites did not differ significantly in their soil microbial community composition in early May prior the nun moth population peak [31]. Average annual temperature was 9.2 and 10.8 • C and average annual precipitation was 611 and 474 mm for the study sites in 2013 and 2014, respectively (German Federal Meteorological Service (DWD) and Climate Data Center (CDC), Weather Station Lindenberg (Station ID: 3015), 13.07.2018, see also Supplementary Figure S1; for a description of site properties, see [6,31]). We measured the CO 2 -C and N 2 O-N fluxes across one year (August 2013-July 2014), i.e., on three dates in 2013 (August-October with n = 18 for each date) and five dates in 2014 (March-July with n = 30 for each date).…”
Section: Field Measurementmentioning
confidence: 87%
“…T. fibrillosa occupied twice as many seedlings in K2 than in REF, while C. geophilum showed an opposite trend. REF was characterized by the presence of Lactarius, Russula, and Cortinarius species, associated with healthy forests [20,36,37], with some were still found in K1. A similar trend was detected by Peter et al [33], who found T. fibrillosa increased its abundance on seedlings in a locality affected by air pollution with increasing damage intensity, while Russula and Lactarius species preferred sites with lower damage levels.…”
Section: Discussionmentioning
confidence: 99%